A survey: Hybrid SDN. (15th December 2017) - Sandhya,; Sinha, Yash; Haribabu, K.
Abstract: A full deployment of Software Defined Networking (SDN) paradigm poses multi-dimensional challenges viz., technical, financial and business challenges. Technical challenges of scalability, fault tolerance, centralization guarantees exist. Financial challenges of budget constraints, non-availability of phased transition model exist. Business challenges like acceptability, building confidence among network operators etc. exist. Therefore, a direct and sudden transition from legacy networks to pure SDN seems unlikely. A hybrid deployment of SDN can be one of the plausible intermediate paths, primarily because it provides an environment where both legacy and SDN nodes can work together. Thus, an incremental deployment strategy can be developed. Further, hybrid SDN can enforce the benefits of both the traditional networks and SDN paradigm. Hybrid SDN deployment has many advantages including adaptability to budget constraints, central programmability of the network, fallback to time-tested legacy mechanisms and so on. But there are challenges specific to hybrid models, like added complexity of running multiple paradigms together, realizing cooperation between control planes, etc. We envision that more research work is needed to maximize the benefits and limit the drawbacks. In this paper, we present a comprehensive survey of hybrid SDN models, techniques, inter-paradigm coexistence and interaction mechanisms. Firstly, we delineate an overview of hybrid SDN roots and consequently we discuss the definition, architectural pillars, benefits and limitations of hybrid SDN. Further, we categorize the different models under various headings, that can be used for deploying hybrid SDN. Next, we do a comparative analysis of each model. We discuss implementation approaches in each model and challenges that may arise in the deployment of hybrid SDN.